Cytomegalovirus‐Productive Infection Is Associated With Acute Coronary Syndrome. Issue 8 (20th August 2016) - Nikitskaya, Elizaveta; Lebedeva, Anna; Ivanova, Oxana; Maryukhnich, Elena; Shpektor, Alexander; Grivel, Jean‐Charles; Margolis, Leonid; Vasilieva, Elena
Abstract : Background: Although an association between human herpesvirus (HHV) infection and atherosclerosis has been suggested, the data supporting such an association are controversial and, in most cases, are based on serological evidence or on the presence of cell‐associated HHV DNA, which do not report about actual viral replication. We quantified the DNA of all 8 types of HHVs in plasma, in which their presence is evidence of viral replication. Methods and Results: Using quantitative real‐time polymerase chain reaction, we evaluated the presence of HHV DNA in blood samples obtained at the time of hospitalization from 71 patients with acute coronary syndrome, 26 patients with stable coronary artery disease, and 53 healthy volunteers and in atherosclerotic plaques of 22 patients with peripheral artery disease who underwent endarterectomy. HHV‐5 (cytomegalovirus [CMV]) was the only HHV with a level that was higher in acute coronary syndrome patients than in the control group and that correlated with the level of high‐sensitivity C‐reactive protein. The numbers of effector memory T cells positively correlated with the numbers of CMV genome copies in carotid arteries plaques, whereas the numbers of central memory T cells negatively correlated with CMV copy numbers. Conclusions: Of all HHV levels, only CMV was higher in patients with stable coronary artery disease and acute coronary syndrome than in the healthy group, and its load correlated with the level of high‐sensitivity C‐reactive protein. The level of CMV in atherosclerotic plaques correlated with the state of immunoactivation of lymphocytes in plaques, suggesting that the reactivation of CMV may contribute to the immune activation associated with the progression of atherosclerosis.